Rapid on-line non-destructive detection of the moisture content of corn ear by bioelectrical impedance spectroscopy - Pengfei, Zhao; Hanlin, Zhang; Dongjie, Zhao; Zhijie, Wang; Lifeng, Fan; Lan, Huang; Qin, Ma; Zhongyi, Wang (International Journal of Agricultural and Biological Engineering, 2015)
Moisture content of corn directly affects its quality and storage time, and the rapid on-line detection of the moisture content of corn ears not threshed or in vivo in the fields is required. Because of the special shape of corn ear, the rapid, low cost and non-destructive bioelectrical impedance measurement is more suitable for its moisture content detection. Using the four-electrode method with the Agilent E4980A precision LCR meter, the electrical impedance spectroscopies of the sweet corn ears and waxy corn ears at different moisture contents were acquired. The frequency range of the detection was from 20 Hz to 2 MHz and to enhance the contact, the attached-type electrodes were wrapped in cotton soaked with 0.1% NaCl solution. The impedance data over the frequency range from 300 Hz to 5 kHz were used to obtain the parameters of the bio-impedance Cole-Cole model. The results showed a good linear correlation (coefficient of determination R2=0.960) between the equivalent parallel resistance R∞ of sweet corn ear and the moisture content value determined by standard chemical method. The research proved that the bioelectrical impedance spectroscopy can be used for detecting the moisture content of corn ear. Keywords: moisture content, non-destructive detection, bioelectrical impedance spectroscopy, corn ear DOI: 10.3965/j.ijabe.20150806.1238 Citation: Zhao P F, Zhang H L, Zhao D J, Wang Z J, Fan L F, Huang L, et al. Rapid on-line non-destructive detection of the moisture content of corn ear by bioelectrical impedance spectroscopy. Int J Agric & Biol Eng, 2015; 8(6): 37－45.